Evaluation of the fibroblast growth factor receptor 1 (FGFR1) in experimental autoimmune encephalomyelitis (EAE) - Rajendran, Ranjithkumar; Justus Liebig University Giessen (My University, 2014)
Fibroblast growth factors (FGFs) exert diverse biological effects by binding and activation of specific fibroblast growth factor receptors (FGFRs). Recent studies on the function of FGF2 in MOG35-55-induced experimental autoimmune encephalitis (EAE) showed that systemic deletion of FGF2 leads to a more severe disease course, increased lymphocyte and macrophage infiltration and decreased remyelination. In the present study the in vivo function of the corresponding receptor Fgfr1 was characterized using an oligodendrocyte-specific genetic approach. Plp/CreERT:Fgfr1fl/fl mice were administered tamoxifen to induce conditional Fgfr1 deletion in oligodendrocytes (referred to as Fgfr1ind-/-). In MOG35-55-induced EAE the Fgfr1ind-/- mice show a delayed onset of disease, less maximum disease severity and enhanced recovery. Decreased lymphocyte and macrophage/microglia infiltration, and myelin and axon degeneration are found in Fgfr1ind-/- mice. In acute EAE downregulation of proinflammatory cytokines such as TNF-alpha, IL-1beta and IL-6, in chronic EAE downregulation of the CX3CL1/CX3CR1 pathway is seen in Fgfr1ind-/- mice. Furthermore, increased expression of BDNF, TrkB (neurotrophic tyrosine kinase receptor, type 2) and decreased expression of Lingo-1 are found in Fgfr1ind-/- mice. Fgfr1 ablation in oligodendrocytes showed increased TrkB expression in whole lysate of cortex and spinal cord. These data suggest that impaired signalling via oligodendroglial Fgfr1 has a beneficial effect on MOG35-55-induced EAE. These findings on the oligodendroglial Fgfr1 pathway may offer a new target for developing therapy in multiple sclerosis.
Bewertung des Fibroblasten-Wachstumsfaktor-Rezeptors FGFR1 bei experimenteller autoimmuner Enzephalomyelitis (EAE)
Keywords: EAE; FGF; FGFR1; oligodendrocytes; MS; ddc:570